Patrick Sellar and the Highland Clearances : homicide, eviction, and the price of progress - Richards, Eric, 1940-2018 (Polygon at Edinburgh, 1999)
"Patrick Sellar, fiercest advocate and enforcer of the Highland Clearances, is possibly the most hated man in Scottish history. It is said even now that the grass will not grow on his grave. In the first biography of Sellar ever published Eric Richards uses contemporary sources to reconstruct his life and times, telling a dramatic story that will allow the reader to rejudge the man - for better or for worse."--Jacket